Safety, immunogenicity, and immune persistence of two inactivated COVID-19 vaccines replacement vaccination in China: An observational cohort study - Wang, Xiaoqi; Deng, Yao; Zhao, Li; Wang, Lei; Fu, Zhenwang; Tang, Lin; Ye, Fei; Liu, Qianqian; Wang, Wenling; Wang, Siquan; Hu, Bo; Guan, Xuhua; et al. (Vaccine, 2022)
To mitigate a national shortage of WIBP-CorV COVID-19 vaccine, China’s regulator approved administering BBIBP-CorV after WIBP-CorV for completion of a primary series. In a pragmatic observational study, we compared immunogenicity and safety of a primary series of WIBP-CorV followed by BBIBP-CorV with a primary series of two doses of BBIBP-CorV. We invited healthy 18–59-years-old adults who had already received either WIBP-CorV or BBIBP-CorV as their first dose in a primary series to participate in this observational cohort study. Subjects who had received WIBP-CorV as their first dose became the observation group; subjects who had received BBIBP-CorV as their first dose became the control group. All participants received BBIBP-CorV as their second dose. We obtained sera 1, 2, and 6 months after second doses for nAb titer measurement by micro-neutralization cytopathic effect assay with SARS-CoV-2 strain HB01, standardized with WHO International Standard for anti-SARS-CoV-2 immunoglobulin. Safety was assessed for the 7 days after administration of second doses. Between March and December 2021, 275 subjects were included in the observation group and 133 in the control group. Neutralizing seropositivity (≥1:4) rates were 98.91 % and 99.25 % at 1 month and 53.16 % and 70.69 % at 6 months. One-month geometric mean titers (GMTs) were 21.33 and 22.45; one-month geometric mean concentrations (GMCs) were 227.71 IU/mL and 273.27 IU/mL. One to two months after vaccination, observation group seropositivity rates and titers were not significantly different to the control group’s. Adverse reaction rates were 11.27 % and 18.80 %, all mild or moderate in severity. Both primary series were immunogenic; immunogenicity of WIBP-CorV followed by BBIBP-CorV was not different than immunogenicity following two doses of BBIBP-CorV for two months after vaccination; safety profiles were acceptable for both regimens. BBIBP-CorV can be used to complete a primary series that started with WIBP-CorV.